Business simulation as a tool to develop the scenario analysis capacity - Prado Roman, Miguel; Prado Roman, Alberto; Paz Gil, Iria (Journal of Management and Business Education, 2021)
In a labour market so saturated with competent professionals and full of business adversities, students feel that the traditional educational system is not enough to enable them to be well prepared to compete efficiently in it. Therefore, in this research we have developed a business simulation game that allows them to delve into several fundamental facets so that they can ensure their professional success: involvement, capacity to analyze the environment, and decision-making capacity. This activity consisted of formulating, through a business competition, three business models with their corresponding web pages, data on their activities and different operating environments for each of them. The participants in this study were students of industrial organization and associated degrees (N = 76). The results of the study have determined that the students have been able to develop their skills in a real environment, as well as to improve their professional skills and their ability to make influential decisions in the management of the company. This simulation has enabled students to cope with real situations in which to apply the knowledge acquired during the career. In this way, students have felt better trained to be compete in the current competitive labour market.